2018
DOI: 10.1002/pld3.69
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic response to increased irradiance correlates to variation in transcriptional response of lipid‐remodeling and heat‐shock genes

Abstract: Plants have evolved several mechanisms for sensing increased irradiance, involving signal perception by photoreceptors (cryptochromes), and subsequent biochemical (reactive oxygen species, ROS) and metabolic clues to transmit the signals. This results in the increased expression of heat-shock response genes and of the transcription factor LONG HYPOCOTYL 5 (HY5, mediated by the cryptochrome photoreceptor 1, CRY1).Here, we show the existence of another response pathway in Arabidopsis. This pathway evokes the SPX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 92 publications
0
11
0
Order By: Relevance
“…The role of ABA in drought tolerance is inevitable because of its critical role in modulating stress responsive gene expression to coordinate plant stress responses, growth, and development under adverse conditions. AtSR45a also participates in ABA signal transduction to modulate abiotic stress responses [5,22,29]. In this study, we found that expression of stress-related genes such as AtDREB2A, AtNCED3, AtKIN1, and AtRD29A were upregulated in transgenic lines compared with control plants, indicating that the overexpression of BrSR45a might induce stress response gene expression in transgenic plants.…”
Section: Discussionmentioning
confidence: 57%
“…The role of ABA in drought tolerance is inevitable because of its critical role in modulating stress responsive gene expression to coordinate plant stress responses, growth, and development under adverse conditions. AtSR45a also participates in ABA signal transduction to modulate abiotic stress responses [5,22,29]. In this study, we found that expression of stress-related genes such as AtDREB2A, AtNCED3, AtKIN1, and AtRD29A were upregulated in transgenic lines compared with control plants, indicating that the overexpression of BrSR45a might induce stress response gene expression in transgenic plants.…”
Section: Discussionmentioning
confidence: 57%
“…Consistent with this assumption, induction of MGD3 transcript was moderate in our experimental setup (Figure 2). Interestingly however, van Rooijen et al (2018) observed upregulation of PHR1 target genes with involvement in lipid remodeling after 1 hour of irradiance increase. Thus, it will be exciting to learn from future experiments whether P i signaling also contributes to the changes that can be seen in the lipid composition of leaves under different light conditions (Yu et al, 2021).…”
Section: Discussionmentioning
confidence: 85%
“…Our study differs from previous studies on high light responses not only because of our use of the “super-natural” magnitude of our high light treatment, but also for the way the treatment was applied. While previous high-light studies involving A. thaliana have employed irradiances ranging from between 150 and 2000 µmol m - 2 s - 1 , all of these studies applied the high light treatment to low light-adapted plants and focused on the response, or acclimation, to the high light [18, 20, 70, 71, 72, 73, 74, 75, 76]. We, on the other hand, focused on the steady-state transcriptional activity in the four species we examined grown from the seedling stage to maturity under either low or high light.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past years, several studies on transcriptional activity in a number of species have increased our knowledge on the response of photosynthesis to irradiances of different intensities or changes in irradiance. It was shown that Arabidopsis thaliana acclimates to high light by increasing expression of heat shock response genes and lipid remodelling genes [18], that rice ( Oryza sativa ) exposed to variations in irradiance associated to field conditions activates a large number of biotic and abiotic stress genes [19], and that barley ( Hordeum vulgare ) expresses genes involved in phenolic compounds accumulation at a higher level with increasing irradiance [20]. However, none of these studies applied a long-term, very high irradiance treatment, similar to what is experienced by plants growing in natural temperate environments during summer months, at high altitude conditions, or in the equatorial region.…”
Section: Introductionmentioning
confidence: 99%